Association between ATG16L1 gene polymorphism and the risk of Crohn's disease. (December 2017) - Zhang, Bei-Bei; Liang, Yu; Yang, Bo; Tan, Ying-Jun
Objective: To perform a meta-analysis to evaluate studies investigating the association between ATG16L1 gene polymorphism and Crohn's disease. Methods: PubMed, Embase and Web of Science databases were searched for all studies focusing on the association of ATG16L1 and Crohn's disease. Combined odds ratios with 95% confidence intervals were calculated for four genetic models (allelic model: G allele versus A allele; additive model: GG versus AA; dominant model: GA + GG versus AA; recessive model: GG versus GA + AA) using either a random effects or fixed effects model. Results: A total of 47 case–control studies involving 18 638 cases and 30 181 controls were included in the final meta-analysis. There was a significant association between ATG16L1 and Crohn's disease for all four genetic models. Significant associations were also shown in subgroup analyses when stratified by study design (population- or hospital-based). Conclusion: In this meta-analysis, the ATG16L1 genotype was significantly associated with the risk of developing Crohn's disease.